Microstructure and properties of nano-fibrous PCL-b-PLLA scaffolds for cartilage tissue engineering - L He (European Cells & Materials, 2009)
Nano-fibrous scaffolds which could potentially mimic the architecture of extracellular matrix (ECM) have been considered a good candidate matrix for cell delivery in tissue engineering applications. In the present study, a semicrystalline diblock copolymer, poly(e-caprolactone)-block-poly(L-lactide) (PCL-b-PLLA), was synthesized and utilized to fabricate nano-fibrous scaffolds via a thermally induced phase separation process. Uniform nano-fibrous networks were created by quenching a PCL-b-PLLA/THF homogenous solution to -20ºC or below, followed by further gelation for 2 hours due to the presence of PLLA and PCL microcrystals. However, knot-like structures as well as continuously smooth pellicles appeared among the nano-fibrous network with increasing gelation temperature. DSC analysis indicated that the crystallization of PCL segments was interrupted by rigid PLLA segments, resulting in an amorphous phase at high gelation temperatures. Combining TIPS (thermally induced phase separation) with salt-leaching methods, nano-fibrous architecture and interconnected pore structures (144±36 mm in diameter) with a high porosity were created for in vitro culture of chondrocytes. Specific surface area and protein adsorption on the surface of the nano-fibrous scaffold were three times higher than on the surface of the solid-walled scaffold. Chondrocytes cultured on the nano-fibrous scaffold exhibited a spherical condrocyte-like phenotype and secreted more cartilage-like extracellular matrix (ECM) than those cultured on the solid-walled scaffold. Moreover, the protein and DNA contents of cells cultured on the nano-fibrous scaffold were 1.2-1.4 times higher than those on the solid-walled scaffold. Higher expression levels of collagen II and aggrecan mRNA were induced on the nano-fibrous scaffold compared to on the solid-walled scaffold. These findings demonstrated that scaffolds with a nano-fibrous architecture could serve as superior scaffolds for cartilage tissue engineering.